Oxygen vacancies and peroxo groups on regular and low-coordinated sites of MgO, CaO, SrO, and BaO surfaces - Di Valentin, Cristiana (2006)
The formation of an oxygen vacancy and the simultaneous re-adsorption of an oxygen atom on regular and low-coordinated (LC) sites (edges and corners) of the surface of alkaline-earth oxides with cubic rock salt structure, MgO, CaO, SrO, and BaO, has been investigated using DFT cluster model calculations. The process corresponds to the formation of a surface Frenkel defect when the vacancy formation energy is partially compensated by the energy gained in the formation of a peroxo group. The structural and electronic properties of vacancies and peroxo groups along the series of alkaline-earth oxides have been analyzed. We found that the role of low-coordinated sites on the surface chemistry of alkaline-earth oxides is of crucial importance for MgO, but decreases for the heavier members. For instance, on BaO the formation of a peroxo group is practically site-insensitive. This is not the case of the vacancy formation, which is always favored on the low-coordinated sites.